The Extent to Which Some of the Infant Formulas Available in Iraqi Markets Conform to the Standards and Meet the Requirements of Ideal Infant Growth - Mohanad Abbood Alhamid (Journal of Global Pharma Technology, 2018)
This study was conducted in the laboratories of the College of Agriculture University of Kufa and the laboratories of the College of Food Sciences University of Al-Qasim Green. To determine the extent to which the specifications of different samples of infant milk formulas available in the local markets of Najaf province meet the standard specifications, meet the requirements of the ideal growth of Infant, and compare them with the overall composition of breast milk. Four replicates of different production batches were used for each model of infant formula. Nactalia1, Dielac1, Evolac1, Celia2, Dielac2 and Sunnybaby2.The results showed a decrease in the amount of energy processed by the milk formulas Dielac1, Celia2 and Sunny baby2, which were 65.48, 63.27 and 65.78 kcal / 100 ml, respectively, compared to the amount of energy provided by the mother to her infant. The amount of protein in all Infant milk formulas with genetic fructose intolerance especially during the first four months of life. It was also observed that the percentage of whey protein in the milk formulas Dielac1, Evolac1 and Dielac2 was similar to that in cow's milk at 17%, 20% and 16%, respectively. But increased to 25% in Celia2 milk and were close to the proportion of breast milk in the milk formula of Sunnybaby2 and Nactalia1 48% and 52%, respectively. It was also found that both mothers and experts accepted all infant milk formulas under study.Keywords: Infant formula, Nitrogen distribution, Sensory evaluation.